The right to housing in the Sustainable City - Pasquotto , Geise Brizotti; Salcedo, Rosio Fernandez Baca (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The right to housing is a fundamental piece to ensure the dignity of the human person. Although it is an independent right, its absence compromises the full exercise of other basic rights, such as health, education, work and leisure. Adequate housing, quality of urban life and social sustainability are intrinsically linked to the ability of the federal, state and municipal government to create laws, execute and supervise compliance with urban regulations for effective and efficient planning. Objective: to go through the legal evolution of the right to housing concept at the international and national levels. Methodology: The work is divided into three axes: the first demonstrates how the right to housing concept was constructed and the second one addresses this issue in the Brazil constitution. The third aims to incorporate public housing policies carried out into the Brazilian legislation analysis. Results: The results aim to verify whether there was a major impact of international and national legislation on public housing policies, with a special focus on federal actions implemented in Brazil.